Inulin dietary supplementation attenuates the stress induced by pursuit/capture/atmospheric exposure and improves innate immune response in hybrid catfish (Pseudoplatystoma reticulatum♀ × Leiarius marmoratus♂) after exposure to Aeromonas hydrophila - do Nascimento Veiga, Pamela Thainara; Rodrigues, Tatiane Auxiliadora Ribeiro; Fantini-Hoag, Letícia; Rodrigues, Robson Andrade; Pilarski, Fabiana [UNESP]; Owatari, Marco Shizuo; Martins, Maurício Laterça; de Campos, Cristiane Meldau (Springer Nature, 2024)
The aim of the study was to evaluate the effects of inulin on stress and innate immunity of hybrid catfish (P. reticulatum × L. marmoratus). A total of 208 juvenile surubim, with initial average weight and length 37.91 ± 5.58 g and 18.51 ± 0.69 cm, were randomly distributed in 16 tanks (100 L) in a 4 × 5 factorial scheme. Inulin was used at four inclusion levels (0% — control, 0.25%, 0.50%, and 0.75%) for 31 days. At the end of period, blood aliquots were collected to characterize time zero. Then, the fish were exposed to pursuit/capture/atmospheric exposure stress for a new blood collection after 0.5 h. Soon after, the fish were exposed to A. hydrophila, and new blood samples were obtained at 3, 6, and 24 h post-challenge. There was a significant interaction on plasma cortisol in 0.50% inulin group. There was a significant reduction in hemoglobin and hematocrit at 24 and 3 h, respectively, after stress management + bacterial challenge. For glucose, a significant increase was observed after stress management (0.5 h) as well as a significant decrease at 6 h after stress management + bacterial challenge. A significant increase in total leukocytes and lymphocytes was observed at 6 h, while thrombocytes increased significantly at 6 and 24 h. No significant interaction was observed in leukocyte respiratory activity. Fish supplemented with 0.50% inulin showed a significant increase in serum lysozyme. The inclusions of inulin at 0.25% and 0.75% provide greater hormone cortisol homeostasis, while inulin at 0.50% improved the immune system of hybrid surubim.
Keywords: Aquaculture; Immune system; Prebiotic; Stress management; Surubim